C++ multithreading cookbook : over 60 recipes to help you create ultra-fast multithreaded applications using C++ with rules, guidelines, and best practices /: over 60 recipes to help you create ultra-fast multithreaded applications using C++ with rules, guidelines, and best practices. (2014) - Unknown
No abstract available